Rational control of WSe2 layer number via hydrogen-controlled chemical vapor deposition. (19th May 2020) - DeGregorio, Zachary P; Myers, Jason C; Campbell, Stephen A
Abstract: Tranistion metal dichalcogenides are a promising family of materials for electronics and optoelectronics, in part due to their range of bandgaps that can be modulated by layer number. Here, we show that WSe2 can be selectively grown with one, two, or three layers, as regulated by a one-step hydrogen-controlled chemical vapor deposition (H-CVD) process involving cyclical pulses of H2 flow. The physical and vibrational properties of the resulting mono-, bi-, and tri-layer WSe2 films are characterized by atomic force microscopy and Raman spectroscopy. Modifying the H-CVD process to include more than three H2 pulses results in thicker WSe2 films, however the thickness of these films is not well controlled and feature small, bulk-like pyramidal islands. Transmission electron microscopy analysis reveals that most of these islands exhibit a spiral structure and appear to be grown via screw-dislocation-driven growth, similar to other works. Therefore, the H-CVD process is demonstrated to be a powerful tool for controlling the layer thickness of WSe2, but its practicality is limited to the few-layer regime.